Everyday prison governance in Myanmar : understanding imprisonment beyond the west - Jefferson, Andrew M.; Yin, Nai Hla; Yar, Lynn Tar (Emerald studies in activist criminology., 2025)
Everyday Prison Governance in Myanmar analyses prison life in Myanmar during a short-lived period of democratic transition. The accounts of former prisoners reveal the realities of everyday life illuminating survival strategies, landscapes of emotion, and power dynamics. Making a significantly different kind of contribution, this is the first in depth, empirically based, systematic study of imprisonment practices in Myanmar between 2015-2020, a period believed by many to herald a new democratic dawn for Myanmar before the subsequent military coup. Based on rich data gathered across four sites and examined collaboratively by a team comprised of experienced prison scholars and a local research team, the authors do not simply document the dynamics of prison governance; they analyse and contextualise them, utilising a bottom-up perspective informed by the most recent scholarly trends on prison governance in the Global South. Filling an important gap in the scholarship about prisons in South East Asia and expanding the scope of the field of prison studies 'beyond the west', the authors provide important counterpoints to dominant understandings of imprisonment based on Western sources.